Characterization of ultrasonic nonlinear properties of interfacial pressure in 110kV integral prefabricated cable intermediate joints - Ouyang, Benhong; Xia, Rong; Wang, Yuli; Yuan, Jianjun; Huang, Kaiwen; Zhao, Peng; Wang, Ge (Frontiers in Physics, 2025)
The interfacial pressure between cable accessories and cable insulation plays a decisive role in the insulation characteristics of the accessories and the long-term reliable operation of the cable. Considering the actual rough contact interface between the cable body and the intermediate joint, a finite element simulation model of stress field-sound field coupling was constructed using points with Gaussian probability distribution. Based on this model, the differences in echo signals in the time domain and frequency domain at different positions of the cable accessories, as well as the differences in echo signals under different interfacial pressures at the same position, were analyzed. Subsequently, the functional relationship between interfacial pressure and nonlinear parameters was fitted. Finally, a nonlinear ultrasonic testing platform was established to measure the interfacial pressure at different positions of the cable intermediate joint, verifying the accuracy of the relationship between interfacial pressure and nonlinear parameters. The experimental and simulation results showed consistent patterns in the time domain and frequency domain of the echo signals, with the nonlinear parameters increasing as the interfacial pressure increased. The experimental results indicated that the detected nonlinear parameter value was around 7.46 × 10−3 (with an error range within 5.80%), corresponding to an interfacial pressure of 0.21 MPa; and the detected nonlinear parameter value was around 6.38 × 10−3 (with an error range within 7.60%), corresponding to an interfacial pressure of 0.16 MPa. The nonlinear parameters can characterize the interfacial pressure at different locations, verifying the validity of the simulation fitting function and providing a new approach for measuring the interfacial pressure of cable accessories.